Conceptual design and multidisciplinary optimisation of power device for solar powered aircraft - Danjuma, Safyanu Bashir (2021)
Solar-powered aircraft is propelled by a photovoltaic cell that converts solar energy into electrical energy. The extra energy is stored in a rechargeable battery for later use when solar energy is not available. The performance of solar-powered aircraft is limited to solar radiation availability, low efficiency of the photovoltaic cell, and low energy density of the rechargeable battery. The research aims to improve the power device sizing, reduce the aircraft's mass, and improve the flight duration for sustainable flight operations for solar-powered aircraft (CLOUD 1). This was achieved using a multidisciplinary optimisation tool, a commercial package ModeFrontier software. Photovoltaic Geographic information system (PVGIS) software was used to obtain a solar radiation model for Malaysia. The model was used to develop both the energy balance and mission path for Malaysia to facilitate the availability and utilisation of solar energy for successful flight operations. Airfoil analysis was conducted. WE.3.55.9.3 airfoil was the best-chosen airfoil used for the wing design, while the empennage design, NACA 0008, was the most suitable. Hence, the latter was used for horizontal and vertical tail design with XFLR5 v6 software's aid. A novel methodology for the power device sizing was developed on MS Excel with 435.48Wh, 540.96Wh, 32, and 70 as the total required electrical energy, available solar energy, number of solar cells required, and the number of batteries required, respectively. The optimisation strategy embraced ModeFrontier software with the goal set to; minimise total electrical energy required, minimise the total mass, and maximise the available solar energy. The optimisation results show that available solar energy was 283.56Wh, the total electrical power required was 228.32Wh, the number of solar cells was 16, and the number of batteries was 36. The total mass of the aircraft was 2.05 Kg, respectively. The optimisation results achieved 53%, 51%, and 26% reductions in the number of solar cells, the number of batteries, and the aircraft's mass. Also, the flight duration was improved by 33%. The optimal configuration was used to design the solar-powered aircraft (CLOUD I).